Utilization of Agricultural Land During the Planting Break in Jorong Mandahiling Nagari Pagaruyung, West Sumatra: Sharia and Legal-Formal Economic Perspectives - Rizal Fahlefi; Alimin Alimin; Indah Fitrah Nauri (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2021)
Abstract: The study aims to explain the pattern and legal perspective of the practice of agricultural land use cooperation during the planting break in Jorong Mandahiling, Tanah Datar Regency, West Sumatra Province. This research uses a case study method which is analyzed qualitatively. The research subjects consisted of 21 land owners and 21 land cultivators. The results showed that there are three patterns of land use cooperation during the planting break in Jorong Mandahiling. Based on three patterns of cooperation, there are three types of contracts that apply from the point of view of sharia economic law, namely: first, leasing on land (kirā’ al-ardh); second, profit sharing system (mudhārabah); and third, combination of profit sharing system and joint venture (mudhārabah musytarakah) with a profit sharing system which does not fulfill the principle of fairness in transactions. Viewed from the perspective of sharia economic law and existing legal-formal, the practice of profit sharing in land use cooperation during the planting break is not fully in accordance with existing provisions, especially in the principle of fairness in transactions, because, two of the three contracts that are practiced are more profitable for land owners and unfair for culvtivators.Abstrak: Penelitian ini bertujuan untuk menjelaskan pola dan tinjauan hukum terhadap praktik kerja sama pemanfaatan lahan pertanian selama masa jeda tanam di Jorong Mandahiling, Kabupaten Tanah Datar, Provinsi Sumatera Barat. Penelitian menggunakan metode studi kasus yang dianalisis secara kualitatif. Subjek penelitian terdiri dari 21 orang pemilik lahan dan 21 orang penggarap lahan. Hasil penelitian menunjukkan bahwa terdapat tiga pola kerja sama pemanfaatan lahan pada masa jeda tanam di Jorong Mandahiling. Dari tiga pola kerja sama tersebut, terdapat tiga jenis akad yang berlaku dari sudut pandang hukum ekonomi syariah, yaitu: pertama, sewa atas tanah (kirā’ al-ardh); kedua, sistem bagi hasil (mudhārabah); dan ketiga, perpaduan sistem bagi hasil dan kongsi (mudhārabah musytarakah) dengan sistem bagi hasil yang tidak memenuhi prinsip keadilan bertransaksi. Ditinjau dari perspektif hukum ekonomi syariah dan legal-formal yang ada, praktik bagi hasil dalam kerja sama pemanfaatan lahan pada masa jeda tanam tersebut belum sepenuhnya sesuai dengan ketentuan yang ada, khususnya dalam prinsip keadilan bertransaksi, karena dua dari tiga akad yang dipraktikkan lebih menguntungkan bagi pemilik lahan dan tidak adil bagi penggarap lahan.